Robô-car: uma abordagem da robótica educacional aplicada ao ensino de física - Moura, Natana Rodrigues de (2019)
This work aims to present the development of an educational product that is used as a teaching tool in the physics classes, suggesting a methodological approach in teaching kinematics, more precisely on concepts related to uniform movement, to high school students from the use of the low cost Educational Robotics. It proposes a manual didactic of development of the prototype, titled Robô-Car, commanded by programming from a Arduino platform, as well as a methodology, in didactic sequence, that consists of a practical part using the robot applied to the study of movement, where students will participate actively, and a theoretical with the subsequent analysis of the data collected. In this first moment we aim to work in a playful, interactive and intuitive the concepts of movement, using Educational Robotics as a tool in the teaching-learning process, considering the rates of variation, its application to the study of motion and the error in the measurement of quantities. In the theoretical part, the ideas addressed in the experiment will be debated from the organization and analysis of the collected data, being the teacher responsible for the orientation, with interventions, increasingly active until the theory is unveiled. In this process, the student will construct a logical sequence of reasoning allowing, based on your knowledge of world, the understanding of the proposed theory. It has been found that the use of Educational Robotics in classrooms is an extraordinary methodological resource, since besides unlimited use, it is also extremely attractive. This characteristic is fundamental, since it excites the students causing greater stimulation both to concentrate and to debate the activities proposed in the room.